2022
DOI: 10.1111/jdv.18259
|View full text |Cite
|
Sign up to set email alerts
|

Erythema multiforme associated with anti‐plakin antibodies: a multicentric retrospective case series

Abstract: Background Erythema multiforme (EM) is a muco‐cutaneous inflammatory disease mainly triggered by herpes simplex virus (HSV) recurrences. Association of EM and circulating auto‐antibodies against plakins (anti‐PLK‐Abs [EM‐PLK+]) has been reported. However, little is known about this subset of EM. Objectives We aimed to describe the clinical and immunological features and response to treatment of EM‐PLK+. Methods We conducted a retrospective multicentric study of EM‐PLK+ selected from the database of the immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…No HSV was detected in bullous pemphigoid [ 43 ]. Antiviral therapy has a controversial efficacy in HSV-induced erythema multiforme [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…No HSV was detected in bullous pemphigoid [ 43 ]. Antiviral therapy has a controversial efficacy in HSV-induced erythema multiforme [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of autoantibodies against envoplakin and periplakin is sensitive to the diagnosis of PNP 58 . These antibodies are also detectable in patients with erythema multiforme 64 . The pathogenicity of antibodies against plakin family members that are localized intracellularly is unclear.…”
Section: Pathogenic Role Of Autoreactive T Cells In Pnpmentioning
confidence: 99%
“… 58 These antibodies are also detectable in patients with erythema multiforme. 64 The pathogenicity of antibodies against plakin family members that are localized intracellularly is unclear. One study reported that purified anti‐desmoplakin antibody from a patient with PNP induced dissociation of keratinocytes in vitro and caused blisters in vivo when transferred to neonatal mice.…”
Section: Pathogenic Role Of Autoreactive T Cells In Pnpmentioning
confidence: 99%